PROFIL KINERJA PENGAWAS MADRASAH - Aisya Maqdisiana; Sumadi Sumadi; Sowiyah Sowiyah (Program Studi Magister Manajemen Pendidikan)
The aim of research is to describe and analyze the recruitment madrassas supervisor, organization, competence and performance of madrassas supervisors. The research method is descriptive qualitative that is based on the theory of phenomenology. The results were: (1) Recruitment of supervisor at the Ministry of religious Madrasah Bandarlampung based on the formation of the Regional Office of the Ministry of Lampung Province, the ministry's executive committee religion that city, in the groove recruitment was also clear. 2) Madrassas supervisors organization has had a clear coordination between the members; 3) Madrassas supervisors have competence which includes personality, managerial supervision, academic supervision, evaluation of educational, social and supervisors. 4) Supervisory Performance Madrassas already running duties and functions in accordance with applicable regulations, Total supervisors in terms of the amount need to be added; 5) Human Resources supervisor madrasas need to be improved in terms of quantity and quality should receive training appropriate to the duties of a madrassas supervisor.Tujuan penelitian ini untuk mendiskripsikan dan menganalisis rekrutmen pengawas madrasah, organisasi pengawas madrasah, kompetensi pengawas madrasah dan kinerja pengawas madrasah. Metode penelitian yaitu kualitatif deskriptif yang didasari teori fenomenologi. Hasil penelitian menunjukkan; 1) Rekrutmen Pengawas Madrasah pada Kementerian Kota Bandarlampung berdasar pada formasi pemetaan Kantor Wilayah Kementerian Provinsi Lampung, sebagai pelaksana yaitu panitia kemenag kota, alur rekrutmen juga sudah jelas. 2) Organisasi Pengawas Madrasah telah mempunyai koordinasi yang jelas di antara anggota pengawas berjalan baik; 3) Kompetensi pengawas madrasah yang meliputi kepribadian, manajerial, akademik, evaluasi pendidikan, dan sosial telah dimiliki pengawas; 4) Kinerja Pengawas Madrasah sudah menjalankan tupoksinya sesuai dengan peraturan yang berlaku, Jumlah pengawas dari segi jumlah perlu ditambah; 5) Sumber Daya Manusia pengawas madrasah dalam hal kuantitas perlu ditingkatkan dan kualitas perlu mendapat pelatihan-pelatihan yang sesuai dengan tupoksi seorang pengawas madrasah.Kata kunci: kinerja, kompetensi, pengawas madrasah, profil